Rol de la Organización de las Naciones Unidas ante el genocidio y violación de derechos humanos por parte del estado de Myanmar en contra de la población Rohingya durante el periodo 2012-2017 - Torres Quevedo, Paola Isabel (2019)
The objective of this research is to analyze the mechanisms used by the United Nations Organization to confront the genocide and violation of human rights against the Rohingya Muslim community in Myanmar, a situation that took a turn from 2012 to 2017 for a series of confrontations and persecutions causing the death of millions of men, women and children, in addition to causing a massive migration of refugees to Bangladesh, unbalancing the peace and security of neighboring States. It is very important to study this topic because the increase in international crimes continues to be a matter of debate in the international community, leaving in evidence that despite the visible atrocities such as the genocide in Rwanda and the genocide in Bosnia in the 20th century, even in the 21st century, international crimes of this type continue to be perpetrated. In this sense, the theory of international regimes will serve as the basis for the case study. To this end, the Charter of the United Nations and the Universal Declaration of Human Rights (UDHR) will be analyzed, in which the United Nations consolidates its commitment to promote and protect the rights of the individual and their dignity, principles that are embodied in the UDHR; besides taking the necessary measures to prevent and eliminate any threat of peace and security. This is to analyze whether the United Nations (UN) regime has complied with the norms established in its Charter and with the principles of the Universal Declaration of Human Rights. Under this same theory, an approach will be made to know what the role of the UN has been and how it has responded to this problem. It is concluded that indeed, the United Nations has not had the scope and sufficient effectiveness to implement a solution in favor of the persecution against the Rohingya minority, which leads us to believe that there are gaps within the current United Nations system.